Conifer Regeneration After Experimental Shelterwood and Seed-Tree Treatments in Boreal Forests: Finding Silvicultural Alternatives - Montoro Girona, Miguel; Lussier, Jean-Martin; Morin, Hubert; Thiffault, Nelson (Frontiers in Plant Science, 2018)
Forest regeneration is a key element in achieving sustainable forest management. Partial harvest methods have been used extensively in temperate broadleaf and mixedwood ecosystems to promote regeneration on poorly stocked sites and to maintain forest composition and productivity. However, their effectiveness in promoting conifer establishment has yet to be demonstrated in unmanaged boreal forests, especially those dominated by black spruce (Picea mariana (Mill.) BSP) where constraints for regeneration differ from those found in more meridional regions. We aimed to evaluate conifer seedling density and dimensions, 10 years after the onset of a gradient of silvicultural treatments varying in harvesting intensities, and to identify the critical factors driving the regeneration process. Study blocks of even-aged black spruce stands in the eastern Canadian boreal forest were submitted to three variants of shelterwood harvesting: a seed-tree harvest, a clear-cut and an untreated control. Shelterwood and seed-tree harvesting were combined with spot scarification to promote regeneration. Shelterwood and seed-tree harvesting produced a density of conifer regeneration sufficient to maintain forest productivity, but they did not promote seedling growth. Black spruce was the predominant species in terms of regeneration density, with proportions 3–5× higher than that for balsam fir (Abies balsamea (L.) Mill.). Ten years after treatment, seed-origin black spruce seedlings were abundant in skidding trails, while layers dominated the residual strips. Balsam fir density was not influenced by treatment nor by tree position relative to skidding trails. Balsam fir and black spruce had different responses to treatment in terms of height and diameter, the former exhibiting a better growth performance and larger diameter in the residual strips. Spot scarification created micro-sites that had a significant impact on the regeneration process. Overall, our results support that shelterwood and seed-tree harvesting combined with scarification enable adequate regeneration in black spruce stands, confirming these treatments as viable silvicultural alternatives to clear-cutting when required by sustainable forest management objectives.